2002
DOI: 10.1200/jco.2002.20.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Insulin and Outcome in Early-Stage Breast Cancer: Results of a Prospective Cohort Study

Abstract: Fasting insulin level is associated with outcome in women with early breast cancer. High levels of fasting insulin identify women with poor outcomes in whom more effective treatment strategies should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
303
0
15

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 630 publications
(324 citation statements)
references
References 48 publications
6
303
0
15
Order By: Relevance
“…15,16 Insulin stimulates the synthesis of androgens in the ovary. 19 Recently, high serum insulin levels have also been implicated, 13 with relative risks of the same magnitude as in the present study in which, however, the association was not statistically significant, possibly due to the small study size. Several studies have indicated that overweight patients, often characterized by hyperinsulinemic insulin resistant status and high sex hormones levels, have poorer survival.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…15,16 Insulin stimulates the synthesis of androgens in the ovary. 19 Recently, high serum insulin levels have also been implicated, 13 with relative risks of the same magnitude as in the present study in which, however, the association was not statistically significant, possibly due to the small study size. Several studies have indicated that overweight patients, often characterized by hyperinsulinemic insulin resistant status and high sex hormones levels, have poorer survival.…”
Section: Discussionsupporting
confidence: 42%
“…4 Oophorectomy and antiestrogenic treatment reduce breast cancer incidence 5,6 and the incidence of recurrence in breast cancer patients. 7,8 Several studies have also suggested that overweight, 2,9 weight gain during adjuvant treatment, 10 -12 hyperinsulinemia 13 and increased androgenic activity 14 -16 are associated with increased breast cancer recurrences. In the present study, we followed up women enrolled in a previous dietary intervention trial aimed at reducing sex hormone levels in postmenopausal breast cancer patients 17 to examine the relationship between serum hormone levels and cancer recurrence.…”
mentioning
confidence: 99%
“…35,36 The explanation given by the studies finding a stronger association between the MD and the receptor-positive BC is that the hormonal pathway is involved, as the MD has been reported to decrease endogenous estrogens 37 and increase sex hormone-binding globulin levels, 11 thereby decreasing the concentration of circulating estrogens and risk of BC. 14 The MD pattern encompasses a combination of foods and nutrients which may affect hormone receptor subtypes differentially.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is hypothesized that visceral obesity increases both insulin and insulin-like growth factors(IGF-I, IGF-II) which stimulate the synthesis of sex steroid hormones [3] which are involved in the regulation of normal and malignant growth of epithelial breast cells [8;9]. Fasting serum insulin concentration has been directly associated with an increase in both distant recurrence and death in women previously treated for breast cancer [10]. In addition, it has been postulated that obese women may be under-dosed in terms of chemotherapy and/or radiation treatment, resulting in reduced therapeutic response [11;12].…”
Section: Introductionmentioning
confidence: 99%